2001
DOI: 10.2135/cropsci2001.411189x
|View full text |Cite
|
Sign up to set email alerts
|

Determining Genetic Similarities and Relationships among Cowpea Breeding Lines and Cultivars by Microsatellite Markers

Abstract: Cowpea [Vigna unguiculata (L.) Walp] is an important grain legume crop grown for its protein rich grains. It is an inexpensive source of protein in the diets of people in sub‐Saharan Africa. The International Institute of Tropical Agriculture (IITA) has been working on the improvement of cowpea for more than 30 yr. Over 60 countries receive cowpea cultivars improved by IITA for testing and adoption where needed. Many of these cultivars have identical parentage but look very different morphologically when grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
146
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 55 publications
13
146
0
1
Order By: Relevance
“…Genetic variations observed in some of the landraces are very narrow because it might have resulted during the long cultivation history of the species, as an adaptation to the local agroclimatic conditions and may be result of narrow genetic base (Seehalak et al 2006). Li et al (2001) also reported low genetic diversity in cowpea using SSR markers. In the long run, these could have resulted in locally adapted genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variations observed in some of the landraces are very narrow because it might have resulted during the long cultivation history of the species, as an adaptation to the local agroclimatic conditions and may be result of narrow genetic base (Seehalak et al 2006). Li et al (2001) also reported low genetic diversity in cowpea using SSR markers. In the long run, these could have resulted in locally adapted genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used marker systems are restriction fragment length polymorphism (RFLP) (Soller and Beckmann, 1983), random amplified polymorphic DNA (RAPD) (Williams et al 1990), amplified fragment length polymorphism (AFLP) (Vos et al 1995), inter simple sequence repeats (ISSRs) (Zietkiewicz et al 1994) and microsatellites or simple sequence repeats (SSRs) (Becker and Heun, 1994). Among them to characterize DNA variation patterns within species and among closely related taxa in Vigna species have been RAPD (Ba et al 2004;Dikshit et al 2007), AFLP (Sivaprakash et al 2004;Seehalak et al 2006;Yoon et al 2007;Fang et al 2007), RFLP (Kaga et al 2000), ISSR (Ajibade et al 2000), SSRs (Li et al 2001;Dikshit et al 2007) and sequence tagged microsatellite site (STMS) (Phansak et al 2005).…”
mentioning
confidence: 99%
“…By means of only five out of 27 polymorphic SSR markers Li et al (2001) [36] distinguished 88 of 90 cowpea breeding lines. For the complete set of 27 primers, between two to seven alleles were detected per primer, but the primers differed strongly in their PIC (polymorphic information content) which ranged between 0.02 and 0.73 (average: 0.45) [36].…”
Section: Simple Sequence Repeats (Ssrs)mentioning
confidence: 99%
“…For the complete set of 27 primers, between two to seven alleles were detected per primer, but the primers differed strongly in their PIC (polymorphic information content) which ranged between 0.02 and 0.73 (average: 0.45) [36]. Using the same primer set, Diouf and Hilu (2005) [37] found SSR markers to be a more powerful tool than RAPDs to elucidate the relationships between cowpea local cultivars and breeding lines from Senegal.…”
Section: Simple Sequence Repeats (Ssrs)mentioning
confidence: 99%
“…Ohwi and Ohashi) (Wang et al, 2004), cowpea (Vigna unguiculata (L.) Walp.) (Li et al, 2001, Kongjaimun et al, 2012 and common bean (Phaseolus vulgaris L.) (Buso et al, 2006, Blair et al, 2003, Gaitán-Solís et al, 2002, Guerra-Sanz 2004, together with 8 polymorphic AFLP markers generated from 4 primer combinations. The genetic linkage map was constructed using Join Map version 3.0 software with a minimum LOD threshold of 3.0 and maximum recombination frequency of 0.50.…”
Section: Linkage Map and Qtl Analysismentioning
confidence: 99%